Impaired inhibitory reno-renal reflex responses in chronic kidney disease - Rahman, Ahmed A.; Hildreth, Cara M.; Milliken, Phil; Hassan, Sarah; Sridhar, Arun; Phillips, Jacqueline K. (Frontiers in Physiology, 2025)
The renal afferent nerves serve as physiologic regulators of efferent renal sympathetic nerve activity (rSNA) as part of the inhibitory reno-renal reflex. Dysregulation of this reflex response may promote sympathoexcitation and subsequent hypertension under pathologic conditions such as chronic kidney disease (CKD). We have undertaken an in-depth characterization of reno-renal reflex function in CKD using an anesthetized rodent model with concurrent physiological outflows assessed. Using anesthetized male Lewis Polycystic Kidney (LPK) rats and normotensive Lewis controls, we investigated the cardiovascular [blood pressure (BP), heart rate (HR) and sympathetic responses (recorded from renal and splanchnic nerves (r/sSNA)] to renal capsaicin (50 µM) and direct electrical stimulation of the whole renal nerve. In Lewis rats, intra-pelvic renal capsaicin injection resulted in a depressor, bradycardic, and sympathoinhibitory response in sSNA with no significant change in rSNA. In contrast, the same stimulus led to a pressor and sympathoexcitatory response in the LPK group. In Lewis rats, low-intensity electrical stimulation (0.2 ms pulses, 15 μA, 2–40 Hz) of the renal nerve elicited a depressor response and bradycardia with concurrent sympathoexcitation (sSNA), whereas high-intensity (150 µA) stimulation induced a biphasic depressor/pressor response and tachycardia. In LPK rats, low-intensity renal nerve electrical stimulation triggered a biphasic depressor/pressor BP response, tachycardia, and sympathoexcitation. High-intensity stimulation similarly caused a biphasic depressor/pressor BP response and tachycardia. The magnitude of the sSNA response and both phases of the blood pressure response was higher in LPK compared to Lewis. All responses showed some degree of frequency dependency. Our results suggest the inhibitory reno-renal reflex is impaired in CKD, with dominance of excitatory reflex response. However, a depressor component remained that could be targeted using implantable neurotechnologies to lower blood pressure in CKD patients safely and effectively.